2020
DOI: 10.1002/mp.14635
|View full text |Cite
|
Sign up to set email alerts
|

A Benchmark for automatic noise measurement in clinical computed tomography

Abstract: Purpose: Assessment of image quality directly in clinical image data is an important quality control objective as phantom-based testing does not fully represent image quality across patient variation. Computer algorithms for automatically measuring noise in clinical computed tomography (CT) images have been introduced, but the accuracy of these algorithms is unclear. This work benchmarks the accuracy of the global noise (GN) algorithm for automatic noise measurement in contrastenhanced abdomen CT exams in comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…First, it is well known that standard deviations within ROIs incompletely reflect the degree and quality of image noise in a CT dataset and contain no information about its frequency distribution [10]. Nevertheless, this parameter is frequently chosen in image quality studies on clinical CT datasets and some excellent recent work has emphasized the close relationship between this simple parameter and more comprehensive measures of image noise for the types of image noise typically encountered in clinical CT scans [11,12]. Second, the mice in our study were scanned without any other attenuating objects in the gantry-except for X-ray transparent casing and the patient table.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is well known that standard deviations within ROIs incompletely reflect the degree and quality of image noise in a CT dataset and contain no information about its frequency distribution [10]. Nevertheless, this parameter is frequently chosen in image quality studies on clinical CT datasets and some excellent recent work has emphasized the close relationship between this simple parameter and more comprehensive measures of image noise for the types of image noise typically encountered in clinical CT scans [11,12]. Second, the mice in our study were scanned without any other attenuating objects in the gantry-except for X-ray transparent casing and the patient table.…”
Section: Discussionmentioning
confidence: 99%
“…Whether phantom‐based image quality tests of deep learning reconstruction are even relevant is an open question. A broader discussion of potential applications in quality control and standardization enabled by the automatic noise measurement is presented elsewhere 14 …”
Section: Discussionmentioning
confidence: 99%
“…The GN algorithm accuracy found in this study is more or less consistent with previous studies: Ahmad et al reported a percent RMS error of 8.6% in the validation study of the GN algorithm applied to abdomen CT examinations. 14 Christianson et al found a percent F I G U R E 4 Scatterplot of GN versus head size…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations